Why students do not use Facebook? Reasons behind non-use and perceptions of users - Kekić, Aleksandra (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2015)
There is more and more research dedicated to users of social networking sites. While our understanding of users grows, there is few studies dealing with users who decided to shut down their accounts or with users who never opened them. For that reason the object of this research are students who do not use social networking site Facebook – the reasons behind non-usage, as well as their perceptions of the site and its users. The research is based on the uses and gratification theory that is adapted to social networking sites. Empirical material consists of 20 semi-structured in-depth interviews with the students of the University of Novi Sad, because in this age group Facebook is very popular. We wanted to show that those who do not use Facebook turn to alternative means of keeping in touch with those who use the network, but also that they are not deprived of information available to Facebook users. In order to determine the reasons why they do not use Facebook, particular attention was paid to the perceptions of privacy on the social networking site. The conclusion is that students have the knowledge and technical conditions to access to the social networking site, but they do not have the need to use it. They fulfil their needs for interpersonal communication, entertainment and information in alternative ways, giving priority to other services on the Internet and to communication by phone or ‘"face to face’. What students see as especially negative side of Facebook is the invasion of privacy through publication of photos and personal information.